Albumin binding as a potential biomarker of exposure to moderately low levels of organophosphorus pesticides - Tarhoni, Mabruka H.; Lister, Timothy; Ray, David E.; Carter, Wayne G. (Informa Healthcare, 2008)
We have evaluated the potential of plasma albumin to provide a sensitive biomarker of exposure to commonly used organophosphorus pesticides in order to complement the widely used measure of acetylcholinesterase (AChE) inhibition. Rat or human plasma albumin binding by tritiated-diisopropylfluorophosphate ((3)H-DFP) was quantified by retention of albumin on glass microfibre filters. Preincubation with unlabelled pesticide in vitro or dosing of F344 rats with pesticide in vivo resulted in a reduction in subsequent albumin radiolabelling with (3)H-DFP, the decrease in which was used to quantify pesticide binding. At pesticide exposures producing approximately 30% inhibition of AChE, rat plasma albumin binding in vitro by azamethiphos (oxon), chlorfenvinphos (oxon), chlorpyrifos-oxon, diazinon-oxon and malaoxon was reduced from controls by 9+/-1%, 67+/-2%, 56+/-2%, 54+/-2% and 8+/-1%, respectively. After 1 h of incubation with 19 microM (3)H-DFP alone, the level of binding to rat or human plasma albumins reached 0.011 or 0.039 moles of DFP per mole of albumin, respectively. This level of binding could be further increased by raising the concentration of (3)H-DFP, increasing the (3)H-DFP incubation time, or by substitution of commercial albumins for native albumin. Pesticide binding to albumin was presumed covalent since it survived 24 h dialysis. After dosing rats with pirimiphos-methyl (dimethoxy) or chlorfenvinphos (oxon) (diethoxy) pesticides, the resultant albumin binding were still significant 7 days after dosing. As in vitro, dosing of rats with malathion did not result in significant albumin binding in vivo. Our results suggest albumin may be a useful additional biomonitor for moderately low-level exposures to several widely used pesticides, and that this binding differs markedly between pesticides.